2023
DOI: 10.3390/w16010045
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hydrochemical Characteristics, Spatial Evolution, and Driving Forces of River Water in Jinjiang Watershed, China

Yuchen Zhu,
Hongjie Yang,
Yong Xiao
et al.

Abstract: Rivers are an important source of water in humid regions, but their availability is greatly limited by water chemistry. In order to accurately identify the changes in river water chemical composition, the compositional analysis method (CoDA) is proposed from the perspective of compositional data analysis theory, which considers the geochemical riverine system as a whole and detects the compositional changes of the entire watershed. The basic data analysis is carried out by traditional analysis methods, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Based on the national water quality data and field investigations conducted in the East and West Jinjiang between 2020 and 2023, it was observed that the pH and DO values in the East Jinjiang River were significantly higher than those in the West Jinjiang River, while the nutrient concentrations showed the opposite trend. These findings aligned with the results obtained by Zhu et al (2024) [31]. The differences in pH values between the West and East Jinjiang Rivers may be attributed to variations in water chemistry in the two watersheds, which showed that the water chemistry in the East Jinjiang River was dominated with an abundance of HCO 3 − Ca type, and the water in the West Jinjiang River was rich in SO 4…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Based on the national water quality data and field investigations conducted in the East and West Jinjiang between 2020 and 2023, it was observed that the pH and DO values in the East Jinjiang River were significantly higher than those in the West Jinjiang River, while the nutrient concentrations showed the opposite trend. These findings aligned with the results obtained by Zhu et al (2024) [31]. The differences in pH values between the West and East Jinjiang Rivers may be attributed to variations in water chemistry in the two watersheds, which showed that the water chemistry in the East Jinjiang River was dominated with an abundance of HCO 3 − Ca type, and the water in the West Jinjiang River was rich in SO 4…”
Section: Discussionsupporting
confidence: 91%
“…The differences in pH values between the West and East Jinjiang Rivers may be attributed to variations in water chemistry in the two watersheds, which showed that the water chemistry in the East Jinjiang River was dominated with an abundance of HCO3 − Ca type, and the water in the West Jinjiang River was rich in SO4 2− [31]. Furthermore, the relatively high nutrient concentrations in the West Jinjiang River could be linked to the extensive use of fertilizers in the tea plantations surrounding the river, as well as domestic and mine pollution [31]. TN and TP concentrations in the Jinjiang River, during early spring, often exceeded eutrophication thresholds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations